Radical spaces : venues of popular politics in London, 1790-1845 - Parolin, Christina (ANU E Press, 2010)
"Radical Spaces explores the rise of popular radicalism in London between 1790 and 1845 through key sites of radical assembly: the prison, the tavern and the radical theatre. Access to spaces in which to meet, agitate and debate provided those excluded from the formal arenas of the political nation-the great majority of the population-a crucial voice in the public sphere. Radical Spaces utilises both textual and visual public records, private correspondence and the secret service reports from the files of the Home Office to shed new light on the rise of plebeian radicalism in the metropolis. It brings the gendered nature of such sites to the fore, finding women where none were thought to gather, and reveals that despite the diversity in these spaces, there existed a dynamic and symbiotic relationship between radical culture and the sites in which it operated. These venues were both shaped by and helped to shape the political identity of a generation of radical men and women who envisioned a new social and political order for Britain."--Publisher's description